2010
DOI: 10.5301/jva.2010.5774
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Peritoneal Dialysis Catheter Survival: A 9-Year Single-Center Study in 315 Patients

Abstract: PURPOSE To review the peritoneal dialysis (PD) catheter outcomes at our center and assess factors affecting the catheter survival. METHODS We carried out a retrospective study on 315 patients who had their first PD catheter placed between January 2001 and September 2009 at the UT Southwestern/DaVita Peritoneal Dialysis Clinic at Dallas, Texas. Medical records were reviewed for demographic and clinical information of the patients. The primary end point of the study was PD catheter failure, defined as removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 22 publications
4
58
0
1
Order By: Relevance
“…We report an overall catheter survival rate comparable with previous reports of laparoscopic or open placement [8,[11][12][13], with an average of 80% survival at 2 years. Gadallah et al [12] showed that a peritoneoscopically placed catheter (using Y-TEC) had fewer complications and higher survival rates compared with those placed by an open technique.…”
Section: Discussionsupporting
confidence: 73%
“…We report an overall catheter survival rate comparable with previous reports of laparoscopic or open placement [8,[11][12][13], with an average of 80% survival at 2 years. Gadallah et al [12] showed that a peritoneoscopically placed catheter (using Y-TEC) had fewer complications and higher survival rates compared with those placed by an open technique.…”
Section: Discussionsupporting
confidence: 73%
“…None of the other demographic (age, gender, race) or clinical characteristics (body mass index, diabetic status, co-morbidities, previous abdominal surgeries) or any infections (peritonitis, exit site, or tunnel) were found to be signifi cantly associated with PD catheter survival. 45 Our study suggests that, contrary to the general perception, morbid obesity, multiple abdominal surgeries, the presence of co-morbidities, and advanced age should not be considered barriers to patient selection for PD. Inclusion of the surgeon as a part of the multidisciplinary team caring for CKD and ESRD patients can lead to long-term success and growth of a PD program.…”
Section: Growing a Pd Programmentioning
confidence: 86%
“…We have demonstrated excellent catheter survival rates at our center. 45 In a retrospective study of 315 patients examining various risk factors associated with the survival of fi rst PD catheters placed at our center between January 2001 and September 2009, we observed 1-year, 2-year, and 3-year PD catheter survival rates of 92.9%, 91.9%, and 91.1%, respectively. On further investigation of different variables in our study, we observed that PD catheter-related non-infectious complication was the single covariate that signifi cantly reduced the catheter survival time.…”
Section: Growing a Pd Programmentioning
confidence: 99%
See 2 more Smart Citations